2-(4-Bromobenzenesulfonamido)benzoic acid - Arshad, Muhammad Nadeem (International Union of Crystallography, 2009)
In the title compound, C(13)H(10)BrNO(4)S, the dihedral angle between the benzene rings is 82.75 (15)°. An intramolecular N—H⋯O hydrogen bond generates an S(6) ring motif. In the crystal structure, two molecules form an R (2) (2)(8) centrosymmetric dimer through a pair of O—H⋯O hydrogen bonds. Intra- and intermolecular C—H⋯O hydrogen bonds are also observed.